Etnobotani Tumbuhan Ritual dalam Tradisi Tosan Aji Madakaripura : Eksplorasi Pengetahuan Lokal Masyarakat di Singosari, Malang - Fannia Zulfa Marella; Fika Fitriani; Vicke Indriani Christina; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to document and preserve the local knowledge of the Singosari community, Malang Regency, East Java in utilizing plants for the Tosan Aji Madakaripura tradition. A qualitative descriptive approach was used in this study, where data were collected through semi-structured interviews, observation, and documentation. Key informants were determined using a purposive sampling technique, then additional informants were selected using snowball sampling. The data obtained were then analyzed descriptively with the stages of data reduction, data presentation, and conclusion drawing. The results showed that there were 25 plant species from 19 families dominated by tree habitus with the most widely used part being the trunk for carving and extracting. Plants used in this tradition have different philosophical meanings that reflect the reasons for their use in the tradition. The conservation status of most plants is included in the category of least concern, meaning that their populations are still stable, and there are conservation efforts by the community through cultivation. The implementation of the Tosan Aji Madakaripura tradition demonstrates that various plant species are not only used practically but also possess philosophical meanings that represent the relationship between humans and nature. This finding emphasizes that traditional plant use must be balanced with conservation-based management to maintain the sustainability of biological resources.